The Entrepreneur and Effective Conflict Management in a Business Environment - Opeyemi, Iroye Samuel; Ajeh, Deborah Oluwaseun (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
In every living society where there is interactions and relationships, certain general phenomenon cannot be found wanting and prominent among these is ‘’Conflict’’. Conflict, though generally understood to be a state of misunderstanding has been perceived in different ways by different thoughts, and it may not only be detrimental in a deep sense of consideration as the occurrence of same may give rise to positive values and ethics than can govern every human relationship depending on the perception of the involving parties. Literature reviews extensively deals with a lot of items that deals with conflict but little attention has been placed on the influence of an entrepreneur in either sustaining the conflict or eradicating it. This study using analytical method of research through Literature Review particularly examines the person and operations of an Entrepreneur in relation to dealing with conflict situations in a business place. This study postulates that business place conflicts can be easily avoided where the entrepreneur is well tutored and skillful in the art of Conflict Management. The findings and recommendations in this study will help to enlighten entrepreneurs on strategic conflicts management in an organization. Keywords: Business, Conflict, Entrepreneur, Organisation